STUDENTS’ PERSPECTIVES ON READING CIRCLES WITH LOCAL CULTURAL NARRATIVES: EVIDENCE FROM JUNIOR HIGH SCHOOLS IN BELU [PERSPEKTIF SISWA TERHADAP LINGKARAN MEMBACA DENGAN NARASI BUDAYA LOKAL: KAJIAN PADA SEKOLAH MENENGAH PERTAMA DI BELU] - Maria Goreti Djehatu; Priscilla Maria Assis Hornay; Elvis Albertus Bin Toni; Maria Agustina Maia Pinto (Universitas Pelita Harapan, 2026)
This study investigates junior high school students’ perceptions of reading circles using local cultural texts in Belu, Indonesia. Drawing on culturally responsive pedagogy and collaborative learning principles, the intervention involved 110 eighth-grade students who participated in a reading circle activity using translated Belu folk stories. After the activity, students completed a Likert-scale survey measuring enjoyment, cultural relevance, comprehension support, confidence, and motivation to continue reading. The results show consistently positive perceptions across all indicators. A total of 85% of students agreed or strongly agreed that reading circles were enjoyable, while 80% reported that the local stories felt culturally familiar and engaging. Similarly, 85% indicated that the cultural familiarity of the stories helped them understand the English text more easily. Increased confidence was also reported, with 80% of students feeling more capable of reading English texts after the activity. Although motivation to read more English stories was slightly lower, 80% of students still expressed willingness to continue reading similar texts. While the findings are based on self-reported perceptions, the current study highlights that integrating reading circles with local narratives can strengthen students’ motivation, comprehension, and confidence while affirming cultural identity. The approach is therefore recommended as an effective and culturally responsive strategy for EFL instruction in Indonesian junior secondary schools and other multilingual learning environments. Abstrak Bahasa Indonesia Studi ini menyelidiki persepsi siswa SMP terhadap penggunaan reading circles dengan teks budaya lokal di Belu, Indonesia. Berlandaskan pedagogi responsif budaya dan prinsip pembelajaran kolaboratif, intervensi ini melibatkan 110 siswa kelas VIII yang mengikuti kegiatan reading circle menggunakan cerita rakyat Belu yang telah diterjemahkan ke dalam bahasa Inggris. Setelah kegiatan, siswa mengisi kuesioner skala Likert yang mengukur aspek kesenangan membaca, relevansi budaya, dukungan pemahaman, kepercayaan diri, serta motivasi untuk terus membaca. Hasil penelitian menunjukkan persepsi positif secara konsisten pada seluruh indikator. Sebanyak 85% siswa menyatakan setuju atau sangat setuju bahwa kegiatan reading circle menyenangkan, sementara 80% merasa bahwa cerita lokal tersebut akrab secara budaya dan menarik. Selain itu, 85% siswa mengakui bahwa keakraban budaya membantu mereka memahami teks bahasa Inggris dengan lebih mudah. Peningkatan kepercayaan diri juga terlihat, dengan 80% siswa merasa lebih mampu membaca teks berbahasa Inggris setelah kegiatan. Meskipun motivasi untuk membaca lebih banyak cerita berbahasa Inggris sedikit lebih rendah, 80% siswa tetap menyatakan kesediaan untuk melanjutkan membaca teks serupa. Meskipun temuan ini didasarkan pada persepsi yang dilaporkan oleh siswa sendiri, studi ini menegaskan bahwa mengintegrasikan reading circles dengan narasi lokal dapat meningkatkan motivasi, pemahaman, dan kepercayaan diri siswa sekaligus menguatkan identitas budaya. Pendekatan ini direkomendasikan sebagai strategi yang efektif dan responsif budaya dalam pengajaran EFL di SMP Indonesia serta konteks pembelajaran multilingual lainnya.